2014
DOI: 10.1007/s11356-014-3617-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of PPCPs in the marine environment: a review

Abstract: Little research has been conducted on the occurrence of pharmaceuticals and personal care products (PPCPs) in the marine environment despite being increasingly impacted by these contaminants. This article reviews data on the occurrence of PPCPs in seawater, sediment, and organisms in the marine environment. Data pertaining to 196 pharmaceuticals and 37 personal care products reported from more than 50 marine sites are analyzed while taking sampling strategies and analytical methods into account. Particular att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(74 citation statements)
references
References 112 publications
0
66
0
3
Order By: Relevance
“…Clover Point Horse Mussel tissue PPCP concentrations (single sample results; reported on a dry weight basis; Table 6) were higher than those observed in wild marine organisms elsewhere (Dodder et al, 2014;Arpin-Pont et al, 2016;Meador et al, 2016). However, most concentrations fell quickly with distance from the CLO outfall diffuser, similar to the MAC PPCP sediment patterns.…”
Section: Clover Point Horse Musselsmentioning
confidence: 62%
See 3 more Smart Citations
“…Clover Point Horse Mussel tissue PPCP concentrations (single sample results; reported on a dry weight basis; Table 6) were higher than those observed in wild marine organisms elsewhere (Dodder et al, 2014;Arpin-Pont et al, 2016;Meador et al, 2016). However, most concentrations fell quickly with distance from the CLO outfall diffuser, similar to the MAC PPCP sediment patterns.…”
Section: Clover Point Horse Musselsmentioning
confidence: 62%
“…Very near the sewage outfalls (<200 m), environmental concentrations within sediment and resident Horse Mussel tissue were high, sometimes exceeding maximum concentrations observed elsewhere in the natural environment (Dodder et al, 2014;Arpin-Pont et al, 2016;Meador et al, 2016) but not necessarily those observed at heavily anthropogenic areas. However, within the IDZ of both outfalls, water column contamination was minimal with only three PPCPs being detected.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Sewage pollutants such as fecal-related microorganisms, micropollutants, organic matters, and nutrients are transported and discharged into water bodies through CSOs during heavy rainfall events [1][2][3]. These contaminants can potentially pose health risks to humans as well as marine organisms [4][5][6]. Consequently, more precise studies on the distribution of CSO pollutants in receiving waters are necessary.…”
Section: Introductionmentioning
confidence: 99%